Pakistans Military and its Strategy - Shalini Chawla; CHAWLA (Shalini) (New Delhi KW Publishers Pvt Ltd, 2009)
his book is an attempt to fill a critical void in our knowledge in understanding Pakistan s military which on one side began to dominate the power structure of the country and at another sought a unique strategy to apply force for ideological and political goals
Keywords: Military Science; Pakistan Navy; Pakistan Army; Pakistan Airforce; Pskistan Political, Economic. Military Trends